Silver nanoparticles associated with a polyphosphate and fluoride enhance the prevention of enamel demineralization and impact on dual-biofilm adhesion - Mendes-Gouvêa, Carla Corrêa [UNESP]; Danelon, Marcelle [UNESP]; Vieira, Ana Paula Miranda [UNESP]; do Amaral, Jackeline Gallo [UNESP]; de Souza Neto, Francisco Nunes [UNESP]; Gorup, Luiz Fernando; Camargo, Emerson Rodrigues; Delbem, Alberto Carlos Botazzo [UNESP]; Barbosa, Debora Barros [UNESP] (Elsevier, 2022)
Objectives: The aim of this study were to produce a multifunctional nanocomposite combining silver nanoaparticles (Ag), sodium trimetaphosphate (TMP) and fluoride (F), to investigate its effect on dental enamel demineralization and on biofilms of Streptococcus mutans and Candida albicans. Methods: Bovine enamel blocks were submitted to five pH cycles and treated 2x/day with 100 ppm F, 225 ppm F, 100 ppm F + 0.2%TMP or 100 ppm F + 0.2%TMP+10% Ag (100F/TMP/Ag). Next, surface hardness loss (%SH), integrated loss of subsurface hardness (ΔKHN), enamel fluoride (F) and calcium (Ca) concentration were determined. Biofilms from single and dual species of S. mutans and C. albicans were treated with 100F/TMP/Ag, Ag or chlorhexidine gluconate for 24 h. The antibiofilm effect was evaluated by colony-forming unit counting and Scanning Electron Microscopy. Results: The nanocomposite reduced 43.0% of %SH and was similar with samples treated with 225F, 100F/TMP and 100/TMP/Ag. The attribute of F and/or TMP in reducing ΔKHN in 5–20 μm was not affected by the addiction of Ag (110F = 225F = 100F/TMP = 100F/TMP/Ag > Negative Control). Further, 100F/TMP/Ag strongly reduced viable cells of S. mutans in dual biofilms (∼5 log10cm2) and structurally affected the biofilms. Conclusion: The 100F/TMP/F promoted a protective effect against enamel demineralization and was able to significantly inhibit the growth of biofilms of S. mutans and C. albicans. Clinical significance: The focus on prevention and non-invasive dental treatment is the most effective and least costly way to improve the population's oral health conditions. We present a nanocomposite for a multiple approach in prevention of caries.
Keywords: Dental caries; Fluoride; Nanoparticles; Polyphosphates; Silver Compounds